2020
DOI: 10.1002/csc2.20356
|View full text |Cite
|
Sign up to set email alerts
|

General and specific combining ability for cane yield and implications for sugarcane breeding

Abstract: General combining ability (GCA) referencing additive genetic effects and specific combining ability (SCA) referencing nonadditive effects have been applied for decades in maize (Zea mays L.) breeding and other crops to produce greater genetic gains in crop breeding. This study examined the magnitude of GCA and SCA for cane yield and evaluated potential for application in sugarcane (Saccharum spp.) breeding. Data were collected from unselected first‐stage breeding populations sourced from the irrigated, midland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…There seem to be evidence of nonadditive gene action for the yield component traits MC and SL as hybrid performance superseded those of both parents. Similar results of nonadditive gene action for the CY and CY components have been reported by Zhou (2021).…”
Section: Discussionsupporting
confidence: 88%
“…There seem to be evidence of nonadditive gene action for the yield component traits MC and SL as hybrid performance superseded those of both parents. Similar results of nonadditive gene action for the CY and CY components have been reported by Zhou (2021).…”
Section: Discussionsupporting
confidence: 88%
“…This means, during a substantial part of the selection program, sucrose content is estimated with a comparatively higher degree of genetic determination or precision compared with cane yield. Studies have also shown that a greater proportion of the variance for cane yield is under nonadditive gene control, whereas for sucrose content it is under additive gene control (Hogarth, 1987; Hogarth et al., 1990; Mishasha et al., 2022; Zhou, 2020) and the narrow‐sense heritability for cane yield is low compared with sucrose content (Wei & Jackson, 2017; Wei et al., 2017). Taken together these observations indicate that progeny performance based on parental selection should be more favorable for sucrose content compared with cane yield.…”
Section: Resultsmentioning
confidence: 99%
“…In sugarcane, the presence of heterosis has been reported on cane yield, yield components, sugar, and juicy parameters. Zhou [46] found that crosses from different heterotic groups resulted in 24 to 42% higher cane yield than those derived from within heterotic groups. Verma and Singh [47] noticed high and positive heterosis on the number of millable canes per clump (60-80%), the number of internodes per cane (30-50%), stalk weight (50-70%), kg-brix (up to 250%), and commercial cane sugar (40-90%).…”
Section: Discussionmentioning
confidence: 99%